Femininity vs. Australianness: The Case of Ada Cambridge - Klepač, Tihana (2009)
In the nineteenth century nation-building projects novel played an important role as the simultaneous consummation of fiction served to create an imaginary community (Anderson). Hence novel was seized by elite men in the nationalist projects. In the process novel was identified with realism, which was considered new, serious art and consequently, great literature. Suffering “ cultural apartheid” (Summers) as a writer of urban romance novels in the predominantly male, realist, nationalist literary tradition of Australia, the work of Ada Cambrigde has for a long time been silenced and devalued, discounted as popular and commercial cultural capital (Sheridan), only documentary value attributed to it. However, a careful analysis of A Marked Man reveals Cambridge’ s unease with the genre, and her attempt at its subversion on both, the level of form and the level of content, in an effort to render a new experience in a form she traditionally had available as a woman writer. The analysis will reveal the novel to be a valuable cultural capital, as it will not only give evidence of its literary merit, but also demonstrate how it formulates an alternative to the nationalist metanarrative – a “ little narrative” (Lyotard) which voices the concerns of urban nineteenth-century Australian women, as well as locate the “ nodal points” (Lyotard) in which it intersects the Australian nationalist metanarrative.
ENG